Pembentukan Moderasi Keagamaan di Perguruan Tinggi Islam - Abdul Haris Abdullah; Shinta Nento (Al-Ulum, 2021)
This study focuses on students' perceptions to explore and measure the elements that form religious moderation. Nine common factors are understood: understanding Islam, sharia balance, values of human beings, plurality in religion, rights of minority groups, national engagement, anti-violence, an attitude of friendship, and educational curricula. The nine factors seem to be interlinked too intimately, and therefore a theme is needed to simplify and make them more operable. This research method is quantitative with the type of explantation research and using a survey approach. The study involved 90 samples. Data analysis techniques of these factors used the help of computer programs such as SPSS software. The results demonstrated that these nine factors could be reduced to produce new names for the three main factors, namely, diversity, peace, and education. The three designations of these factors will help facilitate the approach in an effort to create an understanding of moderation among students in Islamic religious colleges.